Prevalence and Risk Factors Associated With Surgical Site Infections in Kims Hospital of Konaseema District of Andhra Pradesh - Dr.N.Padmaja; Dr. Deborah Purushottam M; Ajith Kumar; Mary Marlapati (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction Surgical site infection (SSI) remains a common and widespread problem, which contributes to significant morbidity and mortality, prolongs hospital stays, and consequently increases healthcare costs.Wound infection can be defined as the invasion of organisms through tissues following a breakdown of local and systemic host defenses, leading to cellulitis, lymphangitis, abscess, and bacteremia. Infections of surgical wounds are called surgical site infections (SSIs)1. SSIs are defined as infections occurring within 30 days after surgery or within one year if an implant is left in place after the procedure and affects either the incision or deep tissue at the operation site 2. The current study aimed to assess the prevalence of SSI and its associated risk factors among patients who underwent any surgical intervention in KIMS Hospital, Amalapuram in Konaseema district of Andhra Pradesh. Methodology After getting Ethics Committee approval, this cross-sectional study carried out over a period of one year from January 2024 to December 2024 in KIMS Hospital of Konaseema district of Andhra Pradesh.. Inclusion criteria All adult patients of both genders above 18 years who underwent surgery and were admitted to the surgical wards during the study period were included in the present study. Exclusion criteria All pediatric cases were excluded from the study. Patients who underwent second surgery at the same site for any reason, patients on immunosuppressant therapy or any known immunodeficiency disease, patients on antibiotics already for any other infections, and patients with infection elsewhere in the body were also excluded from the study. Results A total of 485 patients underwent different types of surgeries, including elective as well as emergency procedures, during the study period. About 29 SSIs were documented, and hence, the overall prevalence of SSI rate during the study period was 5.97% (n =485). The number of cases that developed SSIs in relation to the type of surgery is shown in Table 1. Out of 485 patients who underwent various surgeries, 235 patients underwent abdominal surgeries, 86 pelvic surgeries, 93 bone and joint surgeries and 71 of them underwent ENT surgeries. Out of 235 abdominal surgeries, 20 (8.5%) cases developed SSIs, 4 (4.6%) SSIs in pelvic surgeries, 5 (5.37%) in Bone & joint surgeries. No SSI was recorded in ENT surgeries. In the present study, it was observed that E.coli 9 ( 31%) was the most common isolate followed by Staphylococcus aureus 8 (27.5 %), Klebsiella pneumonia 4 (13.7%), Pseudomonas aeruginosa with 4 (13.5%), Acinetobacter baumanii 3 (10.3%) and least for coagulase negative staphylococci 1 (3.4%). The risk factors of the study population according to the SSI. Most cases of SSI were diagnosed in males (65.5%). Most of the SSIs were diagnosed in emergency surgeries (58.6%). The SSI has been categorized into superficial, deep, and organ SSIs. In the present study, it was observed that 18(62%) had superficial SSI, and 11 (37.9%) had deep ones. Among the individuals with diabetes mellitus, about 55% of them developed SSI. Among those who had a habit of alcoholism, about 48.2% developed SSI. Those who stayed more than seven days,51.7% of them were diagnosed with SSI.